2008
DOI: 10.1111/j.1365-2516.2008.01658.x
|View full text |Cite
|
Sign up to set email alerts
|

The co effect of prophylaxis and radiosynovectomy on bleeding episodes in haemophilic synovitis

Abstract: Prophylactic substitution treatment and radiosynoviorthosis have a leading role in preventing irreversible haemophilic arthropathy. The aim of the study was to evaluate the effects of prophylaxis treatment and radiosynovectomy on the length of intervals between subsequent haemorrhages in haemophilic patients. Thirty-three joints were treated with radiosynovectomy in 28 patients with bleeding disorders. (90)Y colloid was used in knees and (186)Re colloid for elbows, shoulders and ankles. Twenty patients were on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
3
0
1
Order By: Relevance
“…Regarding the number of bleeding episodes, our results, in line with previous studies have demonstrated the effectiveness of RS in reducing haemorrhagic frequency. The number of haemarthrosis events reduced by 71.13%, from 582 to 168, this being a statistically significant reduction ( P < .001).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the number of bleeding episodes, our results, in line with previous studies have demonstrated the effectiveness of RS in reducing haemorrhagic frequency. The number of haemarthrosis events reduced by 71.13%, from 582 to 168, this being a statistically significant reduction ( P < .001).…”
Section: Discussionsupporting
confidence: 92%
“…9,11,13,14,19,21,22,24 The therapeutic criteria for synoviorthesis are mainly based on the presence of repetitive haemarthrosis not resolved with factor replacement therapy and/or evidence of synovitis (an alteration of the soft tissues, with changes in echostructure) identified using imaging techniques (ultrasound and/or MRI). 8,18,25 Several studies have demonstrated the effectiveness of synoviorthesis in reducing bleeding frequency, [9][10][11]14,19,24,[26][27][28] however, its effects on the degenerative joint process are still unspecified. Thus, the aim of this study was to evaluate the progression of arthropathy in patients with haemophilia treated with RS in the Haemostasis and Thrombosis Unit (UHT) of the University and Polytechnic Hospital La Fe (Valencia, Spain) as well as to corroborate the effects of this technique with reduction in haemorrhagic episodes in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Joint damage is determined by synovial membrane blood release into the joint, which is responsible for structural joint damage ( Table 2 ). 15 The target joint has been classically defined as one in which at least three or more spontaneous bleeding events have taken place within a 6-month period. 6 Nevertheless, the current improved prophylactic treatments have succeeded in reducing recurrent joint bleeds to such an extent that allowing the occurrence of more than two bleeds with no therapeutic intervention is rather uncommon.…”
Section: Joint Statusmentioning
confidence: 99%
“…Zelo učinkovita je radioizotopna sinovektomija z Y-90 (itrijem) ali z Re-186 (renijevim koloidom). Ima malo stranskih učinkov in se lahko izvede ambulantno (154)(155)(156)(157)(158). Pred posegom zadostuje enkratni dvig manjkajočega faktorja na najmanj 30 % in nato rehabilitacija sklepa za vzpostavitev normalnega stanja (1).…”
Section: Kronični Sinovitisunclassified